Antibacterial molded polymer articles, extruded polymer articles and film polymer articles comprising blend of synergistic components
By embedding synergistic compounds such as copper oxide and zinc borate into polymers, the problems of poor efficacy and insufficient durability of existing antimicrobial agents are solved, achieving a highly efficient and economical antimicrobial solution.
Patent Information
- Application Number
- CN202480020683.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-16
- Filing Date
- 2024-02-07
- Publication Date
- 2025-11-07
AI Technical Summary
Existing antibacterial agents used in finished products suffer from poor antibacterial effects, insufficient durability, and high costs, making it difficult to meet the needs of various application scenarios.
By co-blending antimicrobial metal compounds such as copper oxides with boron compounds such as zinc borate and pH adjuvants to form synergistic compounds, these compounds are embedded in polymers and utilize the release of antimicrobial ions by the particles upon contact with fluids to provide a long-lasting antimicrobial effect.
It achieves improved antibacterial effect, enhanced durability, and reduced production cost, making it suitable for a variety of applications.
Smart Images

Figure CN120916642A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] Antimicrobial articles and compositions include, but are not limited to, molded polymeric articles, extruded polymeric articles, and polymeric films or coatings. The molded polymeric articles, extruded polymeric articles, and polymeric films or coatings can be produced from thermoplastic polymers or thermoset polymers. The antimicrobial molded polymeric articles, extruded polymeric articles, and polymeric films or coatings can comprise a mixture of at least one antimicrobial metal compound and a synergistic compound. For example, in one embodiment, the antimicrobial molded polymeric articles, extruded polymeric articles, and polymeric films or coatings can comprise a polymeric substrate, particles comprising at least one antimicrobial metal compound, and particles comprising a boron compound. The compositions can further comprise at least one pH adjuvant that creates an acidic environment inside the composition. The inventors have surprisingly found that these components create a synergistic relationship within the composition that provides a more tailored, lower cost, and / or higher efficacy antimicrobial polymeric composition or article.
[0002] An embodiment of a method of producing molded polymeric articles, extruded polymeric articles, and polymeric films or coatings can comprise blending at least one antimicrobial metal compound, at least one boron compound, and optionally at least one pH adjuvant in a polymeric resin, extruding or molding the resin to produce an antimicrobial polymeric article. Another method comprises blending at least one antimicrobial metal compound, at least one boron compound, and optionally at least one pH adjuvant in a component of a polymerization reaction, such as a monomer, oligomer, or other raw material, and extruding or molding the reaction mixture as the cross-linking reaction occurs. BACKGROUND
[0003] Metal oxides or other antimicrobial metal compounds include, but are not limited to, copper oxides, copper iodide, copper carbonate, silver oxide, silver iodide, zinc oxide, silver chloride, zinc pyrithione, gold oxide, or combinations thereof. Such antimicrobial metal compounds have broad-spectrum antimicrobial properties and have exhibited antifungal, antibacterial, and antiviral properties. Copper and its compounds can be present in articles, liquid coatings and paints, plastic components, and polymeric materials to impart durable and long-lasting antimicrobial activity to different substrates.
[0004] There is a need for an antimicrobial, antiviral, and / or antifungal agent that is effective, processable, and has other advantageous properties for the production of antimicrobial compositions and articles. SUMMARY
[0005] The polymers can be extruded or molded to produce polymeric articles, such as, but not limited to, molded polymeric articles, extruded polymeric articles, and polymeric films or coatings. Molding processes for producing polymeric articles include, but are not limited to, extrusion molding, compression molding, blow molding, injection molding, and rotational molding. Thermoplastic or thermoset polymers can be extruded or molded to produce an antimicrobial polymeric article.
[0006] Any of these processes and polymers can also be used to produce antimicrobial molded polymeric articles. An embodiment of a method for making an antimicrobial molded polymeric article can include making a polymeric slurry comprising a plurality of antimicrobial particles in a polymeric resin. The particles can include water-insoluble particles including antimicrobial metal compounds that release antimicrobial ions upon contact with a fluid and particles including boron compounds. The method includes molding the slurry to form a molded polymeric article with the particles incorporated in the molded polymer. A portion of the particles in the polymer can be exposed and protrude from the surface of the material and release antimicrobial metal ions upon exposure to water or water vapor, thereby providing antimicrobial activity and efficacy to the molded polymeric material.
[0007] Similarly, an embodiment of a method for extruding an antimicrobial polymeric material can include making a polymeric slurry comprising a plurality of antimicrobial particles in a polymeric resin, wherein the particles include particles including water-insoluble antimicrobial metal compounds that release antimicrobial ions upon contact with a fluid and particles including boron compounds; and extruding the slurry to form a polymeric material with the particles incorporated in the polymer, wherein a portion of the particles in the polymer are exposed and protrude from the surface of the material and release antimicrobial metal ions upon exposure to water or water vapor, thereby providing antimicrobial activity of the polymeric material. Methods for extrusion, molding, and film production are known in the art and can be used to produce antimicrobial, antifungal, or antiviral articles comprising the synergistic compounds described herein.
[0008] In further embodiments, antimicrobial extruded or molded articles comprising a polymer (thermoset or thermoplastic), particles including water-insoluble antimicrobial metal compounds that release antimicrobial ions upon contact with a fluid embedded in the polymer, particles including boron compounds embedded in the polymer, and optionally particles including a pH adjuvant.
[0009] For example, water-insoluble antimicrobial metal particles release antimicrobial metal ions at a certain rate and produce a certain antimicrobial efficacy upon contact with a fluid. The degree of antimicrobial efficacy can vary with the antimicrobial agent, the concentration of the antimicrobial agent in the article or composition, the environment experienced by the antimicrobial article, the physical and mechanical properties of the article, the inert ingredients in the article, and other factors. It can be desirable or necessary to alter the inherent antimicrobial efficacy, inherent antimicrobial durability, or concentration of the antimicrobial compound necessary to provide a desired antimicrobial efficacy and / or antimicrobial durability in some applications of the composition or article. The synergistic blend of particles including water-insoluble antimicrobial metals, particles including boron compounds, and optionally pH adjuvants can alter the release rate and efficacy of the article by providing a combination of antimicrobial metal ions, controlling the pH on the surface of the polymer upon contact with water, creating additional antimicrobial agents, and / or other chemical or mechanical alterations to the antimicrobial article.
[0010] In one embodiment, the antimicrobial metal compound is a copper oxide. The water-insoluble copper oxide particles release at least one of Cu+ions and Cu++ions upon contact with a fluid and are embedded in a polymer, wherein a portion of the particles including the water-insoluble copper oxide are exposed and protrude from the surface of the polymeric material. In such embodiments, the concentration of the water-insoluble copper compound can range from 0.1 wt.% to 45 wt.% of the antimicrobial article or composition. The water-insoluble antimicrobial metal compound can include, but is not limited to, for example, copper oxide, copper chloride, cuprous oxide, copper oxide, copper iodide, copper carbonate, silver oxide, silver iodide, silver chloride, zinc oxide, zinc chloride, zinc pyrithione, gold oxide, or combinations thereof. In another embodiment, which can be more advantageous for certain applications, the concentration of the copper oxide or other antimicrobial metal compound can range from 0.2 wt.% to 20 wt.% of the weight of the article or the composition. Other embodiments can be based on silver compounds such as silver oxide and silver iodide.
[0011] Embodiments can also include particles including at least one boron compound. The at least one boron compound includes, but is not limited to, metal borates, borates, boric acid, sodium borate, compounds that produce antimicrobial metal ions and boric acid upon contact with water, sodium borate, potassium borate, zinc borate, and combinations thereof. The concentration of the boron compound can range from 0.05 wt.% to 45 wt.% of the weight of the antimicrobial composition or the article.
[0012] The synergistic blend can also include particles including a pH adjuvant. The concentration of the pH adjuvant can range from 0.01 wt.% to 6.0 wt.%, or in a more specific embodiment, the concentration of the pH adjuvant ranges from 0.02 wt.% to 2 wt.%. In certain embodiments, the solid pH adjuvant particles are molybdenum oxide.
[0013] Embodiments of an antimicrobial molded article, extruded polymer article, or film can include a polymer; water-insoluble antimicrobial metal particles that release antimicrobial ions upon contact with a fluid, the water-insoluble antimicrobial metal particles having a concentration of 0.01 wt.% to 6.0 wt.%, the water-insoluble antimicrobial metal particles being embedded in the polymer; a metal borate; and optionally a pH adjuvant, wherein the pH adjuvant is embedded in the polymer, and the pH adjuvant changes the pH on the surface of the polymer upon contact with water, thereby modulating the release rate of the antimicrobial ions and controlling the decomposition of the metal borate.
[0014] Antimicrobial molded polymer articles, extruded polymer articles, and polymer films comprising synergistic component blends can include, but are not limited to, for example, personal hygiene containers (bedpans, cups, wash basins, trays), air handling equipment and components, appliances, automotive interiors and surfaces, bags (including laundry bags, trash bags, bedding bags, vacuum bags), barrier fabrics, bathroom fixtures and components, buckets, building materials and components (e.g., residential and commercial wall panels), carpet and mat components and assemblies, cleaning equipment (durable and disposable), cleaning supplies and tools, collection and storage containers and equipment (including plumbing systems, silos, tanks, and processing containers), conveyor belts, earplugs, films for fabrics, flooring materials and components, footwear and footwear components, furniture assemblies and components, gaskets, grease traps, aerospace components and fabrics, hand dryers, insulation and weather stripping, kitchen and bathroom hardware and fixtures, liners, packaging materials, plumbing supplies and fixtures, protective covers (durable and disposable), rain and sun shields (sunshades, sun umbrellas, vehicle coverings), trash containers (baskets, cans, bags), respirator components, sports apparel and equipment, medical tape, industrial tape, commercial tape, tarpaulins and coverings, tools, vehicle components.
[0015] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning that is consistent with their meaning in the context of the relevant art and the present disclosure, and will not be interpreted in an idealized or overly formal sense unless expressly so defined herein.
[0016] In describing the present application, it will be understood that a number of components, parts, techniques and steps are disclosed. Each of these components, parts, techniques and steps has individual benefits and can also be used in conjunction with one or more, or in some cases all, of the other disclosed embodiments and techniques. Accordingly, the description will avoid unnecessary repetition of each possible combination of individual steps. However, the description and claims should be read with an understanding that, where there are descriptions of methods, the methods can be performed in any suitable order of steps, including simultaneous performance of steps, except where the application dictates otherwise. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 Polyester fabric samples containing copper oxide particles and zinc borate particles are shown relative to untreated polyester fabric samples for effectiveness in preventing growth of AN on the surface of the fabric samples: untreated PET fabric control before (Al) and after (Bl) incubation for 4 weeks; Sample No. 4 before (A2) and after (B2) incubation for 4 weeks; Sample No. 7 before (A3) and after (B3) incubation for 4 weeks; Sample No. 8 before (A4) and after (B4) incubation for 4 weeks; Sample No. 10 before (A5) and after (B5) incubation for 4 weeks; Sample No. 11 before (A6) and after (B6) incubation for 4 weeks; Sample No. 12 before (A7) and after (B7) incubation for 4 weeks;
[0018] Figure 2 Polyester fabric samples containing copper oxide particles and zinc borate particles are shown relative to untreated polyester fabric samples for effectiveness in preventing growth of AN on the surface after incubation in SDB for 1 week at 22°C; and
[0019] Figure 3 Color stability is shown, with the graph comparing a prior art PET fabric sample containing (left) 1% copper oxide after exposure to a 10% H2O2 solution to an embodiment of a PET fabric sample containing (right) 0.6% copper oxide, 0.6% zinc borate, and 0.3% molybdenum oxide. DETAILED DESCRIPTION
[0020] Antibacterial molded polymer articles, extruded polymer articles, and polymer films include an antibacterial agent that prevents or inhibits the growth of microorganisms on the surface and microenvironment of the composition or article. Microorganisms can include, for example, bacteria, viruses, fungi, and algae, among others. The inventors have found that the efficacy, durability, zone of inhibition, processability, and other antibacterial properties of such articles can be improved by combining the antibacterial agent with different components to create a synergistic compound blend.
[0021] Antibacterial molded polymer articles, extruded polymer articles, and polymer films include synergistic compounds that increase the antibacterial efficacy to be greater than the efficacy, durability, or other properties of the antibacterial agent alone. The antibacterial efficacy of the antibacterial agent alone and the antibacterial efficacy of the synergistic blend combination including the antibacterial compound alone and potentially synergistic compounds can be measured by determining and comparing the zone of inhibition of the antibacterial compound alone and the blend or by other testing. As used herein, the term "antibacterial agent" means an antibacterial, antifungal, and / or antiviral agent.
[0022] In one embodiment, the synergistic polymer composition includes a polymer, a plurality of antibacterial metal compounds embedded in the polymer, a boron compound, and optionally a pH adjuvant that controls the pH of the polymer composition when in contact with water.
[0023] Embodiments of antibacterial molded polymer articles, extruded polymer articles, and polymer films include at least one particle that includes at least one water-insoluble antibacterial metal compound that releases antibacterial ions when in contact with water. The antibacterial metal compound includes, but is not limited to, for example, copper oxide, cuprous oxide, copper oxide, copper iodide, copper carbonate, silver oxide, silver iodide, silver chloride, zinc oxide, zinc pyrithione, gold oxide, or combinations thereof. In another embodiment, the particle can consist essentially of one antibacterial metal compound selected from the group consisting of, but not limited to, for example, copper oxide, cuprous oxide, copper oxide, copper iodide, copper carbonate, silver oxide, silver iodide, silver chloride, zinc oxide, zinc pyrithione, gold oxide, or combinations thereof.
[0024] Embodiments of antibacterial molded polymer articles, extruded polymer articles, and polymer films can include at least one particle that includes at least one water-insoluble antibacterial metal compound that releases antibacterial ions when in contact with water and a particle that includes a boron compound. Thus, embodiments can also include a polymer substrate, a plurality of antibacterial particles embedded in the polymer substrate, wherein the particles include water-insoluble particles that include antibacterial metal compounds that release antibacterial ions when in contact with a fluid and particles that include a boron compound. A portion of the particles in the polymer substrate are exposed and protrude from the surface of the material and release antibacterial metal ions when exposed to water or water vapor. Such antibacterial molded polymer articles can be, for example, irrigation emitters, furniture, a portion of furniture, or fixtures in a hospital. Typical polymers used in molding processes include, but are not limited to, at least one of a polyolefin, a polyamide, a polyester, a polyethylene, a high-density polyethylene, ABS, or a polypropylene.
[0025] For example, an embodiment of a synergistic polymer composition can include a polymer, a plurality of copper compounds that release copper ions in the presence of water, and zinc borate.
[0026] Highly effective antibacterial compositions include at least one antibacterial metal compound and at least one metal borate (hereinafter "synergistic antibacterial compositions"). Surprisingly, even so, zinc borate does not have significant inherent antibacterial activity. In some embodiments, the antibacterial efficacy of the synergistic antibacterial compositions is found to be greater than the sum of the individual efficacies of its components, but the synergistic compositions can improve other properties in addition to efficacy.
[0027] Embodiments can also include a method of extruding an antibacterial polymer resin to produce an antibacterial extruded polymer article. A method for preparing an extruded antibacterial polymer article can include preparing a polymer slurry including a plurality of antibacterial particles in a polymer resin. The particles include particles including a water-insoluble antibacterial metal compound that release antibacterial ions upon contact with a fluid and particles including a boron compound, and extruding the polymer slurry to form a polymeric material with the particles incorporated in the polymer. A portion of the particles in the polymer are exposed and protrude from the surface of the material and release antibacterial metal ions upon exposure to water or water vapor, thereby providing antibacterial activity of the polymeric material. Examples of extruded articles include, but are not limited to, fibers, tubes, rods, masterbatch chips or pellets, antibacterial particles for filters or tiles, and films, for example. The plurality of antibacterial particles can be in any effective concentration that allows the extruded article and allows the antibacterial, flame retardant, or other desired properties to be effective in the final product. For example, the concentration of the particles can range from 1 wt.% to 45 wt.% of the polymer article. In typical embodiments, the polymer resin can be one of polypropylene, polyethylene, polystyrene, and combinations thereof. Additional polymers can also be used in the molding or extrusion process as described above. For example, the extruded article can be further comminuted into antibacterial polymer particles. The particles can be used as masterbatch or can be incorporated into roofing materials, such as, but not limited to, tiles.
[0028] The particle size distribution of the particles including a boron compound embedded in a polymer or polymeric substrate and the particles including an antibacterial metal compound embedded in a polymer or polymeric substrate can be such that ninety percent of the particles are between 0.2 microns and 20 microns. In some further embodiments, the particle size distribution of the particles can be such that ninety percent of the particles are between 1 micron and 10 microns. In some further embodiments, the particle size distribution of the particles can be such that ninety percent of the particles are between 1 micron and 5 microns. In further embodiments, the average particle size of the particles can be between 2 microns and 4 microns.
[0029] In one embodiment, the antimicrobial molded, extruded article or film comprises particles comprising copper oxide and particles comprising zinc borate. In this embodiment, the particles comprising water-insoluble antimicrobial metal compounds that release antimicrobial ions upon contact with a fluid are the particles comprising copper oxide, and the particles comprising boron compounds are the particles comprising zinc borate.
[0030] In any embodiment of the method can further comprise filtering the slurry to remove any particles that exceed a desired particle size.
[0031] The particles comprising antimicrobial metal compounds and the particles comprising boron compounds can be added to the polymer or polymer reaction mixture in the form of a powder comprising antimicrobial metal compounds, a powder comprising boron compounds, a blend of such powders, a powder comprising particles comprising both antimicrobial metal compounds and boron compounds, or one or more masterbatches comprising particles comprising antimicrobial metal compounds and particles comprising boron compounds. The masterbatches and powders can further comprise other processing agents.
[0032] Proposed Mechanism
[0033] Embodiments of the present invention comprise synergistic compound blends that result in increased antimicrobial efficacy, increased color stability, increased processability, or improvement of other properties of polymer articles, films, fibers, yarns, or other molded or extruded polymer articles. One embodiment of an antimicrobial polymer composition comprises a synergistic component blend, wherein the synergistic component blend comprises at least one antimicrobial metal compound that, for example, increases the antimicrobial efficacy of the polymer composition to substantially that of a polymer composition consisting of the individual components alone. The individual antimicrobial efficacy of the individual antimicrobial compounds and the combined antimicrobial efficacy of the synergistic blend comprising the individual antimicrobial compounds and potentially synergistic compounds can be measured by determining and comparing the zone of inhibition of the individual antimicrobial compounds and the blend in a polymer composition. Improvements in other properties can also be similarly measured and compared.
[0034] A synergistic polymer composition comprises a polymer, particles comprising a plurality of antimicrobial metal compounds embedded in the polymer, and particles comprising a boron compound. For example, a synergistic polymer composition can comprise a metal borate and a copper oxide.
[0035] For example, one embodiment of a synergistic polymer composition can comprise a polymer, a plurality of copper compounds that release copper ions in the presence of water, and particles comprising zinc borate. While not wishing to be bound by the disclosed mechanism, in this embodiment, however, it is postulated that zinc borate (ZnB3O4(OH)3) does not consistently dissolve in water at room temperature and reversibly hydrolyzes to insoluble Zn(OH)2and soluble H3BO3(a weak acid).
[0036] One of the synergistic compounds can dissolve incongruently. Many substances dissolve congruently (the composition of the solid matches the composition of the dissolved solute stoichiometrically). However, some substances can dissolve incongruently, whereby the composition of the solute in solution does not match the composition of the solid. This dissolution is accompanied by a change in the "first solid" particles and possibly the formation of a second solid phase. In this embodiment, ZnB3O4(OH)3 hydrolyzes to the second solid phase insoluble Zn(OH)2, which can form an insoluble surface shell on the ZnB3O4 particles, thereby preventing or significantly reducing further dissolution and the formation of soluble borate. Zinc borate ZnB3O4(OH)3 (also described as 2ZnO-3B2O3 3.5H2O) dissolves very little in water and incongruently hydrolyzes to soluble borate and insoluble zinc hydroxide. The borate produced is slightly acidic.
[0037] It is further postulated that, according to the reaction Zn(OH)2+ 2H + → Zn 2+ + 2H2O, the subsequently formed Zn(OH)2 can decompose in the presence of, for example, moisture or a pH adjuvant. This decomposition would produce zinc ions, which can further act as antibacterial ions. As can be seen in the zone of inhibition test, copper oxide alone has some antibacterial efficacy, zinc borate alone has no significant antibacterial efficacy, and the combination of copper oxide and zinc borate has no synergistic antibacterial effect.
[0038] Since the zinc borate hydrolyzes to insoluble Zn(OH)2 on the exposed outer surface of the particle, one would expect no further release of zinc ions. However, a pH adjuvant or water at a desired concentration can control the further decomposition of the insoluble Zn(OH)2, thereby further releasing antibacterial zinc ions. In this way, the polymeric composition or article contains rapidly or slowly released antibacterial metal ions. The metal ions in the metal oxide and metal borate can be further selected to provide antibacterial efficacy by different mechanisms, thereby killing a broader range of microorganisms or thereby combining to more effectively kill microorganisms. In embodiments, the synergistic compounds can be selected to affect or control the release of antibacterial ions, antibacterial efficacy, antibacterial durability, color stability, or other properties.
[0039] Polymer
[0040] The antibacterial article can comprise any polymer. The polymer can be a thermoplastic polymer or a thermoset polymer.
[0041] The polymer is one of the following: polyvinyl chloride, polyolefin, polyethylene, polypropylene, polyethylene phthalate, polydiene, polybutadiene, polyester, polystyrene, polystyrene acrylonitrile, acid polymer, nylon polymer, bakelite, polyolefin, polyethylene, polypropylene, polyallomer, polyacetal, polyamide, polyvinyl chloride, polyester, polyether, polyamide, polyacrylate, polymethacrylate, polyacrylate, acrylonitrile-butadiene-styrene, acrylonitrile styrene acrylate, nylon, polybutylene, polylactic acid, polyurethane, fluoropolymer (such as polytetrafluoroethylene), a blended polymer thereof, or a copolymer thereof.
[0042] In certain embodiments, the polymer is not a polyacid or an anionic polymer. For example, in such embodiments, the polymer does not include a carboxylic acid or carboxylic acid moiety, a sulfonic acid moiety (-SO3H), a phosphonic acid moiety, or a boronic acid moiety.
[0043] The thermoplastic resin can include any thermoplastic resin known in the art and suitable for the envisioned application, for example, but not limited to, such thermoplastic polymers can include olefins (such as low and high density polyethylene and polypropylene), dienes (such as polybutadiene and Neoprene elastomers), vinyl polymers (such as polystyrene, acrylates, and polyvinyl chloride), fluoropolymers (such as polytetrafluoroethylene), and heterochain polymers (such as polyamides, polyesters, polyurethanes, polyethers, polyacetals, and polycarbonates). Thermoset resins include phenol-formaldehyde resins, amino resins, unsaturated polyester resins, epoxy resins, polyurethanes, and silicone polymers.
[0044] Antimicrobial particles
[0045] The antimicrobial metal compound can be any water-insoluble metal compound that releases antimicrobial ions upon contact with water. The antimicrobial metal particles include at least one of an antimicrobial copper compound, an antimicrobial silver compound, an antimicrobial zinc compound, and other antimicrobial metal compounds. For example, the antimicrobial metal compound includes, but is not limited to, for example, copper oxide, copper chloride, cuprous oxide, copper oxide, copper iodide, copper carbonate, silver oxide, silver iodide, silver chloride, zinc oxide, zinc chloride, zinc pyrithione, gold oxide, or combinations thereof. In another embodiment, the particles can consist essentially of one antimicrobial metal compound selected from the group consisting of, including, but not limited to, for example, copper oxide, cuprous oxide, copper oxide, copper iodide, copper carbonate, silver oxide, silver iodide, zinc oxide, zinc pyrithione, gold oxide, or combinations thereof.
[0046] In certain embodiments, the antimicrobial compound or particle can consist essentially of one of, for example, copper oxide, copper chloride, cuprous oxide, copper oxide, copper iodide, copper carbonate, silver oxide, silver iodide, silver chloride, zinc oxide, zinc chloride, zinc pyrithione, gold oxide, or combinations thereof. In another embodiment, the particle can consist essentially of one antimicrobial metal compound selected from the group consisting of including but not limited to copper oxide, cuprous oxide, copper oxide, copper iodide, copper carbonate, silver oxide, silver iodide, zinc oxide, zinc pyrithione, gold oxide. The antimicrobial particles including the water insoluble metal compound can include a functional group or coating. The functional group or coating can aid, for example, handling properties or end product properties.
[0047] Metal oxide powders including at least one of water insoluble copper oxide particles, silver oxide, zinc oxide can be particularly useful in embodiments of antimicrobial compositions or articles. The antimicrobial particles can be antimicrobial particles consisting essentially of, for example, copper oxide, silver oxide, or zinc oxide.
[0048] Molded articles and extruded articles can include at least one water insoluble metal compound at a concentration between 0.1 wt.% and 45 wt.% of the antimicrobial article or composition. The concentration depends on the use, handling, and size of the article.
[0049] In some embodiments, the particles including or consisting essentially of antimicrobial metal compound particles are mechanically held in the polymer matrix and are not ionically bound, hydrogen bonded, complexed, etc. with the polymer. The antimicrobial metal compound can be present in the antimicrobial molded article, extruded article, nonwoven, or film at a concentration of 0.02 wt.% to 10 wt.%, in other embodiments, the concentration can be 0.02 wt.% to 6 wt.%, in other embodiments, the concentration can be 0.05 wt.% to 2 wt.%. The concentration of the antimicrobial metal compound in the article can be based on the desired antimicrobial efficacy, the physical size of the article, the composition of the polymer substrate, the environment in which the article will be used, and other factors.
[0050] Boron compounds
[0051] The synergistic compound or component of the synergistic component blend can include a boron compound. The boron compound can include, but is not limited to, metal borates, silver borate, copper borate, zinc borate, gold borate, sodium borate, calcium borate, potassium borate, borate salts, boric acid, compounds that produce boric acid and antimicrobial metal ions upon contact with water, and combinations thereof. For example, the metal borate decomposes in the presence of water or a pH adjuvant to release antimicrobial ions, even though the metal borate alone does not have significant inherent antimicrobial efficacy. In some embodiments, the boron compound or particle including a boron compound can be replaced by another compound that synergistically interacts with water or a pH adjuvant and an antimicrobial metal compound to increase the efficacy of the polymeric article relative to an article containing only the antimicrobial metal compound.
[0052] The boron compound and its concentration in the article can be selected to control the antimicrobial efficacy, durability of the antimicrobial efficacy, color stability, and / or processability of the polymeric resin to produce a final product by, for example, spinning, drawing, extruding, or molding. The molded articles and extruded articles can include at least one boron compound at a concentration between 0.1 wt.% and 45 wt.% of the antimicrobial article or composition. The concentration depends on the use, handling, and size of the article.
[0053] The boron compound can be present in the antimicrobial molded article, extruded article, nonwoven, or film at a concentration of 0.05 wt.% to 15 wt.%, in other embodiments, the concentration can be 0.2 wt.% to 10 wt.%; in other embodiments, the concentration can be 0.2 wt.% to 5 wt.%.
[0054] pH adjuvant
[0055] A pH adjuvant is a compound that produces an acidic environment upon contact with a fluid to facilitate the hydrolysis of a metal borate, thereby releasing antimicrobial metal ions and / or releasing the metal ions from the antimicrobial composition. The pH adjuvant can decompose or dissociate to form an acidic environment. The pH adjuvant produces a microenvironment in response to an external stimulus, thereby modulating the pH on the surface of the antimicrobial polymeric article. In some embodiments, the decomposition temperature of the pH adjuvant is higher than the compounding and forming (extruding or molding) temperature of the polymeric article. In other embodiments, the pH adjuvant can be formed during compounding, molding, extruding, or other processing steps by decomposition of the compound due to exposure of the compound to elevated temperatures.
[0056] For example, molybdenum oxide decomposes into molybdate and hydrogen cations upon contact with humidity or other sources of water according to the following formula:
[0057] MoO3+ 3H2O → 2H3O++ MoO4 2-
[0058] Other acids will also form hydronium ions that will decompose the metal borate to boric acid and release metal ions. The hydronium ions can accelerate ionization of the metal borate and the antimicrobial metal compound, thereby forming a synergistic antimicrobial product with higher antimicrobial efficacy than the additive antimicrobial efficacy of the individual components.
[0059] In some embodiments, the pH adjuvant is at a concentration of 0.01 wt.% to 5.0 wt.%.
[0060] The pH adjuvant can be selected to control the antimicrobial efficacy, durability of the antimicrobial efficacy, color stability, and / or processability of the polymeric resin to produce a final product by spinning, drawing, extruding, or molding. Examples of pH adjuvants include, but are not limited to, sulfur; acids including, but not limited to, citric acid, phosphoric acid, and the like; acidic salts including, but not limited to, NaH2PO4, ZnCl2, NH4Cl; and acidic oxides including, but not limited to, MoO3, CrO3, Mn2O7, and the like. Thus, the pH adjuvant can be at least one of a compound that creates an acidic environment upon contact with water, an acidic oxide, an acidic salt, molybdenum oxide, chromium oxide, chromium chloride, molybdenum chloride, and combinations thereof.
[0061] The acid dissociation constant, pKa, of an acid can be used to determine whether a compound will create an appropriate acidic environment upon contact with moisture to sufficiently hydrolyze the metal borate and accelerate the release of antimicrobial metal ions (e.g., Cu+ions and Cu++ions from copper oxides) to achieve the desired properties of the polymeric product.
[0062] The polymeric article can further comprise a pH adjuvant package comprising one or more pH adjuvants. The pH adjuvant can comprise, for example, an acid and a buffer. The buffer can be, for example, an acidic buffer or a basic buffer. The acidic buffer can comprise, for example, a weak acid and an acidic salt. Similarly, the basic buffer can comprise, for example, a weak base and a basic salt.
[0063] The method of forming an antimicrobial polymeric composition or article includes a processing step comprising elevating a temperature to mix, cure, melt, or soften the polymer. In certain applications, the decomposition temperature of the pH adjuvant is higher than these processing temperatures, so that all or a portion of the pH adjuvant does not decompose or dissociate during processing.
[0064] Powder blend
[0065] Embodiments of the antimicrobial powder can include synergistic antimicrobial powder blends. The synergistic powders can be blended individually into a polymer resin or aqueous dispersion to produce an antimicrobial composition that can be further processed to form an antimicrobial article. For example, embodiments of the synergistic antimicrobial powder can include particles comprising a water insoluble metal compound and particles comprising a boron compound. The water insoluble antimicrobial powder can include a ratio of metal oxide particles to particles comprising a boron compound of 20: 1 to 1 : 10.
[0066] The synergistic antimicrobial powder can be added to a polymer to produce an antimicrobial polymer article that includes an antimicrobial metal oxide at a concentration of 0.1 wt.% to 5 wt.%.
[0067] The particles comprising an antimicrobial metal oxide can be particles comprising or consisting essentially of one or more of copper oxide, zinc oxide, silver oxide, gold oxide, or combinations thereof. The particles comprising a boron compound can be, for example, particles comprising zinc borate, particles comprising copper borate, particles comprising silver borate, particles comprising calcium borate, particles comprising sodium borate, or combinations of such particles or particles comprising one or more of the boron compounds. In one embodiment, the synergistic antimicrobial powder blend includes particles comprising a water insoluble antimicrobial copper oxide and particles comprising zinc borate.
[0068] In another embodiment, the synergistic antimicrobial powder blend further includes a pH adjuvant. Thus, in one embodiment, the synergistic antimicrobial powder blend can include particles comprising an antimicrobial metal compound, particles comprising a boron compound, and particles comprising a pH adjuvant.
[0069] In particular embodiments, the synergistic powder blend includes copper oxide and zinc borate. In another embodiment, the synergistic powder blend includes copper oxide, molybdenum oxide, and zinc borate.
[0070] Masterbatch
[0071] The antimicrobial masterbatch can be blended with virgin polymer to add the desired color or other properties to the virgin polymer prior to further processing to form an antimicrobial article, film, fiber, yarn, or other molded or extruded article. Methods and processes for producing antimicrobial and / or antiviral polymer masterbatches. The synergistic antimicrobial compounds described herein can be added to virgin polymer to produce a masterbatch, and the masterbatch can subsequently be added to virgin polymer to produce an antimicrobial polymer resin.
[0072] The masterbatch can be extruded into pellets, chips, or formed into other particles for subsequent blending with virgin polymer to add antimicrobial, antiviral, or antifungal properties to the polymer material.
[0073] Embodiments of polymer masterbatches for making antimicrobial polymeric materials can include a thermoplastic resin, an antimicrobial synergistic compound blend including water insoluble antimicrobial metal compound particles (as described herein) and a boron compound (as described herein). The masterbatch can further include a polymeric wax, an agent for occupying the charge of ionic copper oxides, a processing aid or other modifier. The antimicrobial synergistic compound can further include particles including a pH adjuvant.
[0074] A method of producing an antimicrobial article, film, fiber, yarn or other molded or extruded article includes adding a polymer antimicrobial masterbatch to a thermoplastic polymer resin, the polymer antimicrobial masterbatch including a thermoplastic resin, an antimicrobial synergistic compound blend including water insoluble copper oxide particles and zinc borate, and forming the antimicrobial article, film, fiber, yarn and other molded or extruded article.
[0075] A method of producing an antimicrobial article, film, fiber, yarn or other molded or extruded article includes adding a first polymer masterbatch to a thermoplastic polymer resin, the first polymer masterbatch including a thermoplastic resin, an antimicrobial synergistic compound blend including water insoluble copper oxide particles, a pH adjuvant and zinc borate; adding a second masterbatch, the second masterbatch including at least one of the antimicrobial synergistic compounds including water insoluble copper oxide particles, a pH adjuvant and zinc borate, wherein the second masterbatch includes at least one of the synergistic compounds not included in the first polymer masterbatch, and forming the antimicrobial article, film, fiber, yarn and other molded or extruded article.
[0076] For example, the first polymer masterbatch can consist essentially of water insoluble copper oxide particles and zinc borate particles, and the second polymer masterbatch can include a pH adjuvant, such as molybdenum oxide.
[0077] Further embodiments of polymer masterbatches for making antimicrobial polymeric materials can include a thermoplastic resin, an antimicrobial synergistic compound blend including water insoluble metal compound (e.g. copper oxide) particles, and boron compound (e.g. zinc borate) particles, a polymeric wax and an agent for occupying the charge of ionic copper oxides. The antimicrobial synergistic compound can further include a pH adjuvant.
[0078] Antimicrobial, antifungal and / or antiviral masterbatches allow polymeric product manufacturers to economically add antimicrobial and / or antiviral components to polymers during the manufacturing process. More particularly, the present invention relates to an improved method and masterbatch for making antimicrobial and antiviral polymeric materials for a variety of antimicrobial uses.
[0079] Embodiments of antibacterial powder can include synergistic antibacterial powder blends. Synergistic powder blends can be blended into a polymer resin to produce an antibacterial polymer, which can be further processed to form an antibacterial article. Water-insoluble antibacterial powders can include a ratio of metal oxide particles to particles including boron compounds of 20: 1 to 1 : 1. Any antibacterial masterbatch as described herein can include a concentration of, for example, 10 wt.% to 70 wt.% of an antibacterial synergistic compound blend or a subset of antibacterial synergistic compound blends.
[0080] Synergistic antibacterial powders can be added to a polymer resin to produce an antibacterial polymer article including particles including a concentration of, for example, 0.1 wt.% to 5 wt.% of an antibacterial metal oxide.
[0081] An embodiment of a first antibacterial masterbatch can include antibacterial particles including at least one water-insoluble antibacterial metal compound and at least one boron compound embedded in a polymer, wherein the antibacterial masterbatch includes a concentration of 12 wt.% to 50 wt.% of the antibacterial particles.
[0082] An embodiment of a second masterbatch can include molybdenum oxide particles, wherein the second masterbatch includes a concentration of 5 wt.% to 50 wt.% of the molybdenum oxide particles.
[0083] An embodiment of a third masterbatch can include a particle blend including an antibacterial metal compound, a boron compound, and a pH adjuvant, wherein the third masterbatch includes a concentration of 5 wt.% to 50 wt.% of the particle blend.
[0084] A method of producing an antibacterial fiber, nonwoven, film, or other extruded or molded article includes compounding a first antibacterial masterbatch with a polymer. The method can further include compounding the first antibacterial masterbatch, a second masterbatch, and a polymer to produce a polymer article including a metal oxide, a metal borate, and molybdenum oxide.
[0085] Embodiments
[0086] Molded irrigation components and assemblies:
[0087] Embodiments of molded (e.g., irrigation emitters) or extruded articles (irrigation tubing) can be components or portions of or assemblies that include one or more components or layers to enable fluid flow. For example, the articles can be components of an irrigation system. Components of an irrigation system can include any synergistic particle combination described herein. Copper ions from copper compounds such as copper oxides have been shown to prevent root intrusion into irrigation devices.
[0088] In one embodiment, an irrigation device (such as a emitter head, irrigation pipe or a portion of an irrigation pipe) is constructed from a polymer (such as polyethylene) embedded with 5 wt.% to 20 wt.% (such as 10 wt.%) of particles comprising an antimicrobial metal compound (such as cuprous oxide) and 5 wt.% to 20 wt.% (such as 10 wt.%) of a boron compound (such as zinc borate). A plasticizer can be incorporated to achieve the desired mechanical properties of the emitter head or pipe. Optionally, 0.1 wt.% to 1 wt.% of a pH adjuvant can be added to the material. The zinc borate provides resistance to UV radiation, whereby additional UV stabilizers can not be required. The type of irrigation device encompasses emitter heads, irrigation tapes, pipes, tubes, connectors, and the like. The average particle size of both the cuprous oxide powder and the zinc borate powder is in the range of 5 μιη to 10 μιη.
[0089] Assemblies of layers designed to prevent fluid flow from being impeded by insect habitation, root penetration, organic matter, biofilm, or plant material through the managed deposition of metal compounds on, in, and around the microenvironment of the surface. The assembly will also function to inhibit the effects of insect degradation and UV line degradation on the transmission device.
[0090] Examples
[0091] Zone of Inhibition (ZOI)
[0092] Materials.Cupron copper oxide (Cu2O) particles were supplied by Cupron, LLC. Antimony oxide (antimony (III) oxide, Sb2O3, 99%), molybdenum oxide (molybdenum (VI) oxide, MoO3, 99.5%), sodium borate (sodium tetraborate, Na2B4O7, 99.5%), boric acid (H3BO3, 99.5%), zinc oxide (ZnO, 99.5%), sodium molybdate (sodium molybdate (VI) dihydrate, Na2MoO4.2H2O, 99%), calcium chloride (CaCl2, 97%), sodium citrate (Na3C6H5O7, laboratory grade), magnesium sulfate (magnesium sulfate heptahydrate, MgSO4.7H2O, 99%), basic copper carbonate (II) (BCC) were purchased from Fisher. Zinc chloride (ZnCl2, 98%) and zinc bromide (ZnBr2, 98%) were purchased from Thermo Scientific. Zinc sulfate (zinc sulfate monohydrate, ZnSO4.H2O) was purchased from Alpha Chemicals. Zinc borate (Firebrake ZB) was provided by U.S. Borax. Microcrystalline cellulose powder was purchased from LFA Tablet Presses Store. Aspartic acid (98%) was purchased from Acros organics. Molybdic acid, potassium borate, chromium (III) chloride, chromium (VI) oxide, molybdenum (V) chloride, molybdenum disulfide, chromium (III) hydroxide were purchased from Fisher. All chemicals were used as received.
[0093] Sample preparation. Sample granules were prepared from the chemical powders using a DABPRESS 4 ton hydraulic press. The weight percentage of each powder component is detailed in Tables 1 and 2. Microcrystalline cellulose powder (20 wt%) was added as a binder. The chemical powders were mixed by vortexing for 20 seconds to ensure mixing. Then, 0.2 g of the powder blend was added to each well of a 12-well aluminum tablet die (well diameter = 10 mm). The tablet die was then pressed by using the hydraulic press to obtain the sample granules.
[0094] Zone of inhibition (ZOI). E. coli (ATCC 8739) was used to perform ZOI testing. Cultures were streaked on Luria Agar (LB) plates and incubated overnight at 37 °C. A single colony was used to inoculate 10 mL nutrient broth (NB) and the single colony was grown overnight at 37 °C with shaking and obtained (about 10 9A stock suspension of 1-5 colony forming units / mL (CFU / mL). 50 μL of this stock suspension was evenly spread on a tryptic soy agar (TSA) plate (10 cm in diameter). The sample pellets containing copper oxide and adjuvants (§ in triplicate) were then placed on the agar and incubated at 37 °C for 24 hours. The diameter of the zone of inhibition surrounding the sample pellets was measured using a ruler and the results are summarized in Tables 1 and 2.
[0095] Results. As a screening test, Cupron copper oxide particles and their blends with 14 different adjuvants were investigated in ZOI studies to explore potential synergism for antimicrobial effectiveness. The results of this study are summarized in Table 1. The diameter of the ZOI for copper oxide alone against E. coli was found to be 13 mm after incubation at 37 °C for 24 hours.
[0096]
[0097] A significant increase in ZOI size was observed when copper oxide was blended with molybdenum oxide, sodium borate, boric acid, zinc chloride, zinc bromide, zinc sulfate, calcium chloride, molybdate, potassium borate, chromium (III) chloride, chromium (VI) oxide, molybdenum (V) chloride, and molybdenum disulfide, indicating that these chemicals improve the antimicrobial effectiveness of copper oxide against E. coli. Antimony oxide, zinc borate, zinc oxide, sodium molybdate, sodium citrate, magnesium sulfate, aspartic acid, and chromium (III) hydroxide had no effect on the ZOI diameter. These results indicate that: (1) molybdenum oxide, chromium (III) chloride, chromium (VI) oxide, and molybdenum (V) chloride can improve copper ion release by lowering the environmental pH. (2) Zinc borate alone has no effect on the antimicrobial effectiveness of copper oxide. However, the hydrolysis products of zinc borate in an acidic environment, which include boric acid, zinc chloride, zinc bromide, and zinc sulfate, significantly improve the antimicrobial effectiveness of copper oxide. (3) Sodium borate and potassium borate improve the antimicrobial effectiveness of copper oxide as basic salts, indicating that borate ions have a synergistic effect with copper oxide that produces greater antimicrobial effectiveness. Therefore, there is no need to lower the pH to enhance the antimicrobial effectiveness of Cupron copper oxide. In addition to the results discussed above, it was also found that calcium chloride and molybdenum disulfide increase the diameter of the ZOI when blended with copper oxide. Future studies are needed to find the reason for this result.
[0098] The results described above indicate that the hydrolysis product of zinc borate in an acidic environment increases the antibacterial effectiveness of copper oxide. It is reported that molybdenum oxide interacts with water and decreases the pH of the environment. Therefore, the presence of molybdenum can create the environment required for the hydrolysis of zinc borate and thus there can be a synergy between copper oxide, molybdenum oxide and zinc borate in terms of antibacterial effectiveness. To verify this theory, ZOI studies shown in Table 2 were conducted. It was found that the diameters of the ZOIs of copper oxide and molybdenum oxide were 13 mm and 19 mm, respectively. No ZOI of zinc borate was observed. The ZOIs of blends of copper oxide with zinc borate were 12 mm to 13 mm with zinc borate content in the range of 20% to 70% (Table 2, Test Nos. 4, 7, 10 and 13), which indicates that zinc borate alone did not affect the antibacterial effectiveness of copper oxide in this study. The ZOIs of blends of copper oxide with molybdenum oxide were larger than the ZOI of copper oxide alone and the ZOI size increased with increasing molybdenum oxide content (Table 2, Test Nos. 5, 8, 11 and 14). Remarkably, copper oxide,
[0099] The ZOIs of blends of molybdenum oxide with zinc borate were the largest, especially for blends with higher contents of molybdenum oxide and zinc borate (Table 2, Test Nos. 9, 12 and 15). The results confirm the existence of a synergy in copper oxide, zinc borate and molybdenum oxide in terms of antibacterial effectiveness against E. coli.
[0100] To extend the field of application of the synergy described above, BCC was used as the copper oxide in the ZOI studies
[0101]
[0102] Substitutions. As shown in Table 3, BCC was blended with antimony oxide, zinc borate, and molybdenum oxide, and the diameter of the ZOI of the blends was measured. The diameter of the ZOI of BCC alone was found to be 12 mm. The ZOI of the blends of BCC with either antimony oxide or zinc borate was 11 mm (Table 3, Tests 2 and 3), indicating that in this study, zinc borate or antimony oxide did not affect the antibacterial effectiveness of BCC. The ZOI of the blend of copper oxide with molybdenum oxide (20 mm, Table 3, Test 4) was found to be much larger than the ZOI of BCC alone (11 mm, Table 3, Test 1). BCC was then blended with a mixture of antimony oxide and zinc borate (Table 3, Test 5), a mixture of antimony oxide and molybdenum oxide (Table 3, Test 6), and a mixture of zinc borate and molybdenum oxide (Table 3, Test 7). No significant change in the ZOI of BCC was observed (11 mm) after blending with antimony oxide and zinc borate. The ZOI diameter of the blend of BCC with antimony oxide and molybdenum oxide was 18 mm, which was larger than the ZOI diameter of BCC alone, but smaller than the ZOI diameter of the blend of BCC with molybdenum oxide. This result indicates that the enlarged ZOI of the blend of BCC with antimony oxide and molybdenum oxide was primarily due to the synergy between BCC and molybdenum oxide, but the addition of antimony oxide did not have a significant synergy with either BCC or molybdenum oxide for antibacterial effectiveness. The ZOI of the blend of BCC with the mixture of zinc borate and molybdenum oxide was observed to be the largest (25 mm, Table 3, Test 7), indicating that zinc borate and molybdenum oxide can synergistically produce greater antibacterial effectiveness with various copper compounds. Finally, BCC was blended with a mixture of antimony oxide, zinc borate, and molybdenum oxide. The addition of antimony oxide slightly decreased the size of the ZOI to 22 mm, indicating that antimony oxide did not improve the antibacterial effectiveness of the copper compounds.
[0103] Fabric sample preparation
[0104] Cut 2 x 2" polyethylene terephthalate (PET) fabric samples.
[0105] These fabric samples were rolled along their length to form strips. Samples 4, 7, 8, 10, 11, and 12, as well as the untreated PET control, were involved in this test. Table 4. AN was inoculated onto trypsin-soybean agar (TSA) and incubated at 37°C. After 2 weeks of growth, spores were collected by placing 15 mL of DI water in a TSA plate and gently scraping the agar surface with an L-shaped cell spreader. The spore suspension was transferred to test tubes and diluted 10-fold in Sabouraud dextrose broth (SDB) to prepare a stock suspension. The stock suspension (5 μL) was inoculated onto each TSA plate and carefully spread over the entire surface. PET fabric samples were placed on the inoculated TSA plates. Then, 200 μL of the stock suspension was carefully added dropwise to the surface of the fabric sample. Efforts were made to ensure uniform distribution of the stock suspension on the sample surface. The samples were inoculated at 37°C for 1 month to evaluate the effectiveness of the fabric in inhibiting mold growth. Following the incubation period, a 0-4 rating scale was used to determine the antifungal efficacy of the tested material. The rating is described below.
[0106] No growth on sample 0
[0107] 1. Trace amounts of growth (less than 10%) were found on the sample.
[0108] 2. Small amount of growth material (10% to 30%)
[0109] 3-Medium growth (30% to 60%)
[0110] 4. The sample was completely covered by the growth (60%).
[0111] All surfaces showed detectable mold growth, but the amount of growth was significantly less compared to the untreated control. Figure 1 Therefore, in Table 5, samples 4 and 7 are both designated as having an antifungal rate of 2. Sample 8, containing 0.5% copper oxide and 0.5% zinc borate, showed better antifungal properties than samples 4 and 8. Figure 1 A4 and Figure 1 As shown in B4, sample 8 did not completely prevent mold overgrowth, but after 4 weeks of incubation, the overgrowth was almost imperceptible. Therefore, sample 8 was designated as having an anti-mold rate of 1. The introduction of molybdenum oxide further enhanced the anti-mold properties. Sample 10, containing 0.1% copper oxide, 0.6% zinc borate, and 0.3% molybdenum oxide, performed similarly to sample 8. Figure 1, A5 and B5), achieving a 1 rating. Additionally, Sample 11 and Sample 12, which both contained zinc borate and molybdenum oxide, but had a higher content of copper oxide than Sample 10, resulted in a 0 rating for antifungal properties. Notably, no perceptible AN overgrowth was observed on Sample 11 and Sample 12 after the 4-week incubation period. Figure 1 , A6 and B6, A7 and B7
[0112] In summary, the combination of zinc borate with copper oxide significantly improved the overall antifungal properties of the PET fabric samples. This is evident in the results, where the PET sample containing 0.5% copper oxide and 0.5% zinc borate performed better than the samples with 1% copper oxide or 1% zinc borate alone in preventing AN mold overgrowth. These findings suggest that copper oxide and zinc borate have a synergistic effect in inhibiting AN mold growth. Furthermore, the addition of molybdenum oxide further enhanced the resistance of the samples to mold growth. Throughout the study, PET fabric samples with 0.3% molybdenum oxide, 0.6% zinc borate, and 0.3% or more copper oxide were able to completely prevent AN mold overgrowth.
[0113] In summary, the incorporation of zinc borate and copper oxide in PET fabric samples showed a significant improvement in their antifungal properties, and the inclusion of molybdenum oxide further enhanced their effectiveness in inhibiting mold growth. These findings highlight the potential of these additives in developing antifungal PET fabrics.
[0114] Antifungal Study 2
[0115] Experiment. A 1” length of PET fabric sample was carefully cut from a Lawson sleeve and the fiber was placed in a 20 mL clear sample vial with a cap. Involved in this test were Sample 3, Sample 5, Sample 6, Sample 9, and untreated PET control from Table 4. AN was inoculated in Sabouraud Dextrose Broth (SDB) and incubated at 37°C. After 1 week of growth, the AN suspension was transferred to a test tube and diluted 10 times in Sabouraud Dextrose Broth (SDB) to create a stock suspension. The stock suspension (5 mL) was carefully spread over the entire surface of the sample. The cap of the vial was loosely closed to allow for air exchange. The sample was inoculated at 22°C for 1 week to evaluate the effectiveness of the fabric in inhibiting AN mold growth.
[0116] Results . Figure 2 The effectiveness of the PET fabric samples in preventing mold growth is shown in Table 5. After 1 week of incubation at 22°C, perceptible mold growth was observed in several samples, including the untreated PET control, Sample 3, Sample 5, and Sample 6 Figure 2). These samples also exhibited signs of spore production, as indicated by the presence of black spots. This indicates that, under the conditions tested, the use of copper oxide or zinc borate alone was not sufficient to inhibit the growth of AN mold, and in fact, copper oxide even appeared to promote spore production, while zinc borate only partially reduced the production of the spores.
[0117] In contrast, Sample No. 9 showed only slight mold growth, with no detectable black spore production. This indicates that the combination of copper oxide and zinc borate in Sample No. 9 was more effective than the use of copper oxide or zinc borate alone in preventing the growth of AN mold at 22°C.
[0118] These findings are consistent with the results of a previous anti-mold study (referred to as "Anti-Mold Study 1" in this paragraph), which indicated a synergistic pattern between copper oxide and zinc borate in inhibiting the growth of AN mold.
[0119] In summary, the combination of copper oxide and zinc borate exhibited superior anti-mold properties compared to the use of either substance alone. This indicates that there is a synergistic effect between copper oxide and zinc borate, which makes it an ideal choice for preventing the growth of AN mold at 22°C in PET polyester fabric samples.
[0120]
[0121] As shown in Table 6, the copper ion release from one gram of Sample Nos. 10, 11, and 12, which contained 0.6% zinc borate, 0.3% molybdenum oxide, and various amounts of copper oxide, was 4.7 ppm, 11.6 ppm, and 15.9 ppm. The rate of copper ion release increased as the amount of copper oxide increased. Additionally, Sample Nos. 1, 2, and 3, which contained only copper oxide, released copper ions at a rate of 5.1 ppm, 9.8 ppm, and 10.6 ppm per gram of sample. This finding indicates that the rate of copper ion release increased with higher amounts of copper oxide, regardless of the presence of zinc borate or molybdenum oxide.
[0122] Interestingly, Sample No. 11, which contained 0.3% copper oxide, as well as zinc borate and molybdenum oxide, exhibited a copper ion release rate of 11.6 ppm per gram, which was 18% higher than Sample No. 2, which contained the same amount of copper oxide but did not have zinc borate and molybdenum oxide. A similar trend was observed for samples with higher amounts of copper oxide. For example, Sample No. 12, which contained 0.6% copper oxide, as well as zinc borate and molybdenum oxide, had a copper ion release rate of 15.9 ppm per gram, which was 50% higher than Sample No. 3, which had a copper ion release rate of 10.6 ppm / g. With the exception of the sample with 0.1% copper oxide, the addition of zinc borate and molybdenum oxide accelerated the release of copper ions for samples with higher amounts of copper oxide.
[0123] 1" x 1" samples. The compositions of the samples used in this study are shown in Table 4. Samples 1, 2, 3, 5, 9, 10, 11, and 12 were involved in this study. Untreated PET fabric samples were included as controls. The 1" x 1" samples were inoculated with pathogen suspensions and covered with a coverslip and incubated for a 2 hour period. The incubation temperatures and incubation vehicles are summarized in Tables 7 and 8. Immediately following the addition of bacteria, bacteria were recovered from one set of samples by digestion to determine the number of bacteria added to the substrate. Following the 2 hour contact time, bacteria were recovered from another set of samples by digestion. The recovered bacteria were enumerated using the pour plate method by colony forming units.
[0124] The log reduction values were calculated according to the following formula:
[0125] Log Reduction = Log 10 [CFU at 2 hours 对照 ] - Log 10 [CFU at 2 hours 样品 ]
[0126] Results. Table 7 summarizes the antibacterial effectiveness against E. coli under various test conditions. Sample 1, containing 0.1% copper oxide (without zinc borate or molybdenum oxide), showed a log reduction of 4.9 for E. coli when incubated at 37°C and using a 5% nutrient broth (NB) in saline inoculum vehicle. However, when 0.6% zinc borate and 0.3% molybdenum oxide were added to Sample 1, resulting in Sample 10, the efficacy of the substrate increased to a log reduction of greater than 6.9 and an increase of more than 2.0 log reduction. Similar trends were observed for Sample 2, which had 0.3% copper oxide and achieved a log reduction of 6.7, and Sample 11, which had 0.3% copper oxide, 0.6% zinc borate, and 0.3% molybdenum oxide and exhibited a log reduction of greater than 6.9. Both Sample 3 and Sample 12 achieved a log reduction of greater than 6.9, which is the detection limit for this test. These results indicate that the presence of zinc borate and molybdenum oxide enhances the antibacterial effectiveness against E. coli at 37°C with a 5% NB in saline inoculum vehicle, particularly at lower copper oxide concentrations.
[0127] When using a saline inoculum containing 5% tryptic soy broth (TSB), Sample No. 1 with 0.1% copper oxide (without zinc borate or molybdenum oxide) exhibited a 1.6 log reduction against E. coli bacteria. However, upon adding 0.6% zinc borate and 0.3% molybdenum oxide to Sample No. 1 (resulting in Sample No. 10), the efficacy of the substrate increased to a 3.2 log reduction and an increase of 1.6 log reduction. A similar trend was observed for Sample No. 2 with 0.3% copper oxide and Sample No. 3 with 0.6% copper oxide achieving log reductions of 3.3 and 6.2, respectively. Additionally, Sample Nos. 11 and 12 with zinc borate and molybdenum oxide adjuvants, respectively, exhibited log reductions greater than 6.5 and 6.4, respectively. Again, these results indicate that the presence of zinc borate and molybdenum oxide enhances the antibacterial effectiveness against E. coli in a saline inoculum containing 5% NB at 37°C.
[0128] To understand the effect of zinc borate on antibacterial effectiveness, antibacterial studies were performed on Sample Nos. 3, 5, and 9 in synthetic sweat containing 0.5 g / L L-histidine:HCl:H2O, 5 g / L NaCl, 2.2 g / L Na2P04-12H2O, and 15 mL / L 0.1 M NaOH at 21°C. The pH was adjusted to 5.5 using HC1 prior to use. As shown in Table 8, all of the test samples achieved greater than 3 log reduction against E. coli and 5 log reduction against P. aeruginosa. Negligible differences were found between the samples with copper oxide only (Sample Nos. 3 and 5) and the samples with copper oxide and zinc borate for both E. coli and P. aeruginosa. However, a 1.4 log reduction. Further studies need to be conducted to understand why the antibacterial effectiveness was included due to the addition of zinc borate.
[0129] In summary, the presence of zinc borate and molybdenum oxide adjuvants enhances the antibacterial effectiveness against E. coli at elevated temperatures of 37°C, but the addition of zinc borate alone is not able to achieve the same at ambient temperatures.
[0130] Antibacterial study 2
[0131] All test samples (1" x 1") were sterilized under UV light for 1 hour each side inside the cabinet. The test pathogens were inoculated in growth media and allowed to grow to saturation at 37°C in an orbital shaker for 24 hours. After that, the pathogen suspension was diluted to approximately 1.0e8 CFU / mL in an inoculum carrier (IC) containing 5 wt.% M3 Broth, 0.89 wt.% NaCI, and 0.05 wt.% triton. Each sample with foam insert was pre-treated with 1.5 mL of sterilized DI water in two marked petri dishes. The PVC sample debris was then placed on the pre-treated foam. Twenty-two microliters of the bacteria containing IC was then pipetted to the center of each test sample. A plastic coverslip (22 mm) was then placed on top and pressed down gently to coat the IC. The petri dishes were then covered and placed in an incubator at 37°C for 2 hours. After the incubation period, the petri dishes were removed and the test samples with coverslips were placed in a 50 mL conical centrifuge tube containing 17.5 mL of Letheen Broth. The 50 mL conical centrifuge tube was vortexed for 2 minutes and then the solution was serially diluted and plated on nutrient agar. The agar plates were then placed in an incubator at 37°C for 24 hours and then colonies were counted.
[0132] Results. As presented in Table 9, Sample No. 16, which included both copper oxide and zinc borate, exhibited a significant reduction as follows: a log reduction of 3.4 against E. coli, a log reduction of 5 against S. aureus, and a log reduction of 4.5 against P. aeruginosa. These results exceeded the performance of Sample No. 14 (containing only copper oxide) and Sample No. 15 (containing only zinc borate). The data indicates a synergistic antibacterial effect when copper oxide and zinc borate are combined on a PVC substrate.
[0133] Color shift
[0134] Color analysis was performed using a Konica Minolta chroma meter CR-410, first measuring the color of the white reference tile (0, 0, 0) and then measuring the color of the test surface. The color of the test surface was then calculated by subtracting the color of the white reference tile from the color of the test surface. The three values represent, respectively, the degree of lightness objectively measured and calculated for color change. L* quantifies the degree of lightness on a scale of 0 to 100, spanning from black to white; while a* and b* represent chroma without specific numerical limits. Negative a* values correspond to greenish hues, positive a* values indicate reddish hues, negative b* values indicate bluish hues, and positive b* values indicate yellowish hues. Delta (D) represents the difference between the tested surface and the pure white reference. Delta E* acts as a comprehensive measure of the overall difference between the tested surface and the pure white reference, calculated using the following equation:
[0135] Delta E* = ((Delta L*)2 + (Da*) 2 + (Db*) 2 1 / 2
[0136] As shown in Table 10, Sample No. 9, which contains 0.6% copper oxide and 0.6% zinc borate, exhibits the highest lightness (L*). Sample No. 12 exhibits the lowest a* and b* values, which means that the inclusion of 0.6% zinc borate and 0.3% molybdenum oxide effectively mitigates the color shift of copper oxide towards red and yellow. Furthermore, when considering the overall color shift (ΔΕ*), it becomes apparent that Sample Nos. 9 and 12 exhibit values significantly lower than those of Sample Nos. 3 and 5. This indicates that the introduction of zinc borate and molybdenum oxide has a significant impact in reducing the color shift due to the presence of copper oxide.
[0137] Color stability against oxidation
[0138] To investigate the color stability of the PET fabric samples, Sample No. 5 and Sample No. 12 from Table 4 were selected. The investigation aimed to assess the impact of a strong oxidizing agent on the color stability of these samples. Specifically, Sample No. 5 (1.2% copper oxide) and Sample No. 12 (0.6% copper oxide content, as well as 0.6% zinc borate and 0.3% molybdenum oxide) were subjected to an aging process using 10% H2O2.
[0139] During the experiment, both Sample No. 1 and Sample No. 6 were boiled in 10% H2O2 for 3 minutes, followed by a 3-day soak in 10% H2O2 at 37°C. It was observed that both Sample No. 5 and Sample No. 12 experienced shrinkage during boiling. Prior to the aging process, Figure 3 It was shown that the as-is Sample No. 5 had a pinkish hue. However, after undergoing the aging process, the color of Sample No. 5 shifted to a pinkish-gray color. On the other hand, no perceptible color shift was observed for Sample No. 12 after the aging process. This indicates that the combination of copper oxide with zinc borate and molybdenum oxide helps to improve the color stability of PET fabrics, as it remains unaffected by the oxidizing agent.
Claims
1. A method for preparing an antimicrobial polymeric material, the method comprising: preparing a polymeric slurry comprising a plurality of antimicrobial particles in a polymeric resin, wherein the particles comprise water insoluble particles comprising an antimicrobial metal compound that release antimicrobial ions upon contact with a fluid and borate particles or particles comprising a compound that generates borate upon contact with water; and molding the slurry to form a molded polymeric article, wherein the particles are incorporated in the polymer, wherein a portion of the particles in the polymer are exposed and protrude from the surface of the material and release antimicrobial metal ions upon exposure to water or water vapor, thereby providing antimicrobial activity of the polymeric material.
2. The method of claim 1, wherein the particles are between 1 micron and 20 microns in size.
3. The method of claim 1, wherein the particles are introduced into the slurry in an amount of 0.1 wt.% to 45 wt.% of the weight of the polymer.
4. The method of claim 1, wherein the polymeric material is an irrigation emitter.
5. The method of claim 1, wherein the polymeric material is a part of furniture.
6. The method of claim 1, wherein the polymeric material is a fixture in a hospital.
7. An antimicrobial polymeric article comprising: a polymeric substrate; a plurality of antimicrobial particles embedded in the polymeric substrate, wherein the particles comprise water insoluble particles comprising an antimicrobial metal compound that release antimicrobial ions upon contact with a fluid and particles comprising a boron compound, wherein a portion of the particles in the polymeric material are exposed and protrude from the surface of the material and release antimicrobial metal ions upon exposure to water or water vapor.
8. The article of claim 7, wherein at least ninety percent of the antimicrobial particles have a particle size of 1 micron to 20 microns.
9. The article of claim 8, wherein the concentration of the antimicrobial particles ranges from 0.25 wt.% to 45 wt.%.
10. A method for preparing an antimicrobial polymeric material, the method comprising: preparing a polymeric slurry comprising a plurality of antimicrobial particles in a polymeric resin, wherein the particles comprise particles comprising a water insoluble antimicrobial metal compound that release antimicrobial ions upon contact with a fluid and particles comprising a boron compound or particles comprising a compound that generates borate upon contact with water; and extruding the slurry to form a polymeric material, wherein the particles are incorporated in the polymer, wherein a portion of the particles in the polymer are exposed and protrude from the surface of the material and release antimicrobial metal ions upon exposure to water or water vapor, thereby providing antimicrobial activity of the polymeric material.
11. The method of claim 10, wherein the particles are between 1 micron and 20 microns in size.
12. The method of claim 10, wherein the particles are introduced into the slurry in an amount of 0.1 wt.% to 45 wt.% of the weight of the polymer.
13. The method of claim 10, wherein the polymeric material is an antimicrobial polymeric fiber.
14. The method of claim 13, comprising stretching the antimicrobial polymeric fiber.
15. The method of claim 10, comprising spinning the antimicrobial polymeric fiber into a yarn.
16. The method of claim 10, wherein the polymeric material is a tube or a pipe.
17. The method of claim 10, wherein the polymeric material is a film.
18. The method of claim 10, comprising crushing or pulverizing the polymeric material to form polymeric particulates.
19. The method of claim 18, comprising incorporating the polymeric particles into a roofing shingle.
20. The method of claim 18, wherein the plurality of antimicrobial particles is in a concentration range of 4 wt.% to 20 wt.% of the polymeric particulates.
21. The method of claim 18, wherein the polymeric resin is one of polypropylene, polyethylene, polystyrene, and combinations thereof.
22. A method for making an antimicrobial polymeric material, the method comprising: preparing a polymeric resin; blending a plurality of antimicrobial particles into the polymeric resin to produce a polymeric slurry, wherein the particles comprise water-insoluble particles including an antimicrobial metal compound that release antimicrobial ions upon contact with a fluid and particles including a boron compound; and placing the polymeric slurry into a mold to form a polymeric article, wherein a portion of the particles in the polymeric article are exposed and protrude from a surface of the polymeric article and release antimicrobial metal ions upon exposure to water or water vapor.
23. The method of claim 22, wherein the water-insoluble particles including an antimicrobial metal compound that release antimicrobial ions upon contact with a fluid comprise copper oxide and the boron compound comprises zinc borate.
24. The method of claim 22, wherein the polymeric resin comprises at least one of a polyolefin, a polyamide, a polyester, a polyethylene, a high-density polyethylene, ABS, or a polypropylene.
25. An antimicrobial article comprising: a polymer, wherein the polymer is selected from the group consisting of polyethylene terephthalate, a polyolefin, a polyethylene, a polypropylene, a polyvinyl chloride, a polyurethane, a polycarbonate, copolymers thereof, and blends thereof; particles including water-insoluble antimicrobial metal compounds that release antimicrobial ions upon contact with a fluid, the particles being embedded in the polymer, the particles being in a concentration of 0.01 wt.% to 10% wt.%; and particles including a boron compound, the particles being embedded in the polymer, the particles being in a concentration of 0.05 wt.% to 15 wt.%.
26. The antimicrobial article of claim 25, wherein the article is one of a film, a crumb, a tube, a pipe, a panel, and a faux leather.
27. The antimicrobial article of claim 25, wherein the article comprises a layer of a multi-layer article.
28. The antimicrobial article of claim 27, wherein the article comprises at least one layer of foam.
29. The antimicrobial article of claim 25, wherein the boron compound is a basic boron compound.
30. The antimicrobial article of claim 25, comprising a pH adjuvant.
31. The antimicrobial article of claim 30, wherein the pH adjuvant is one of the following: a compound that produces an acidic environment upon contact with water, an acidic oxide, an acidic salt, molybdenum oxide, chromium oxide, chromium chloride, molybdenum chloride, and combinations thereof.
32. The antimicrobial article of claim 25, wherein the particles comprising the boron compound also produce antimicrobial metal ions upon contact with water.
33. The antimicrobial article of claim 25, wherein the particles comprising the boron compound are at least one of the following: a metal borate, boric acid, sodium borate, a compound that produces antimicrobial metal ions and boric acid upon contact with water, sodium borate, potassium borate, zinc borate, and combinations thereof.
34. The antimicrobial article of claim 25, wherein the particles comprising the boron compound are zinc borate particles.
35. The antimicrobial article of claim 25, wherein the water-insoluble particles comprising an antimicrobial metal compound that release antimicrobial ions upon contact with a fluid comprise at least one of the following: copper oxide, copper carbonate, silver oxide, silver iodide, zinc oxide, copper iodide, zinc pyrithione, gold oxide, or combinations thereof.
36. The antimicrobial article of claim 25, wherein the water-insoluble particles comprising an antimicrobial metal compound that release antimicrobial ions upon contact with a fluid are copper oxide particles, and the particles comprising the boron compound are zinc borate particles.
37. The antimicrobial textile fabric of claim 25, comprising molybdenum oxide.
38. A method of producing an antimicrobial article, the method comprising: preparing an antimicrobial polymeric resin, wherein the polymeric resin comprises water- insoluble particles comprising an antimicrobial metal compound that release antimicrobial ions upon contact with a fluid and boric acid particles or particles comprising a compound that produces boric acid upon contact with water embedded in the polymer; and extruding the polymeric resin to form one of the following: a film, a tube, a pipe, polymeric chips, and artificial leather.
39. The method of producing an antimicrobial article of claim 38, wherein polymeric resin comprises a polymer selected from the group consisting of polyethylene terephthalate, polyolefins, polyethylene, polypropylene, polyvinyl chloride, polyurethane, copolymers thereof, and blends thereof.
40. The method of producing an antimicrobial article of claim 38, wherein the polymeric resin comprises particles comprising a pH adjuvant.
41. The method of producing an antimicrobial article of claim 38, wherein the water- insoluble particles comprising an antimicrobial metal compound are copper oxide particles and the particles.